Implementation of Micro Usb Charger TP4056 and Battery Indicator LED in Portable Solar Charge - Donny Auliya Arrohman; Nafis Ainun Fikriyyah (Journal of Natural Sciences and Mathematics Research, 2018)
Mobile is a communication tool that is needed in today's era of globalization. The source of the cellphone's power is the battery which if the power goes out and the battery runs out, it is necessary to charge the battery to turn it back on. In this study, a portable solar panel-based charger was designed as an alternative to charging batteries without using a power source. The method used is research and development where this research produces a product. The results obtained indicate that the highest intensity value at 11:00 WIB is 5986 cd, the highest current value before entering the current stabilizer and voltage amplifier circuit is 0.004 A and the highest voltage is 5 V, for the current value after entering the current stabilizer and amplifier circuit. the overall voltage value is the same, namely 0.002A and 4V. This simple portable solar cell phone charger is able to supply power to the Nokia 215 Dual SIM for 5 hours and 30 minutes. There is an LED indicator on the portable solar charger where during the charging process it will be red, then after it is full it will be blue, and when it is running out it will be orange. ©2018 JNSMR UIN Walisongo. All rights reserved.